Arus Baru Kecenderungan Penafsiran Kontemporer - Musholli Ready (JOURNAL OF QUR'AN AND HADITH STUDIES, 2012)
This article discusses the modern trends in Qur’anic interpretation: the hermeneutical approach and the thematic one. It will first elaborate the origin of hermeneutics, how it has been used by many Muslim scholars, and why many Muslims regarded negatively to this approach. The article then discusses the second approach which is the most used in the Qur’anic interpretation, because, this article argues, it has many advantages, compared to the previous one. At the end, this article proposes the integration between the two approaches